The effect of nutrient intake and protein degradability on the growth and development of Holstein heifers - D.E. Isbell; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1989)
One hundred and twelve Holstein heifers were used from 10 wk until 26 wk of age. They were assigned to receive either 100% or 115% of NRC (1978) recommended nutrients and to be fed either control or extruded SBM. There were no interaction effects between the nutrient amount and type of SBM. Heifers on the higher nutrient amounts gained 205 lb vs 168 lb for the heifers on the lower nutrient amounts. Those on the higher nutrient amounts also had greater increases in height (8.7 vs 7.5 in), length (10.2 vs 8.7 in), and heart girth (12.6 vs 10.6 in). There were no differences in body scores. There were no statistical differences or apparent trends between the extruded and control SBM-fed heifers.; Dairy Day, 1989, Kansas State University, Manhattan, KS, 1989; The 1989 Annual KSU Dairy Day is known as Dairy Day, 1989
Keywords: Dairy Day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-140-S; Report of progress (Kansas Agricultural Experiment Station); 580; Dairy; Nutrient intake; Protein degradability; Holsteins; Growth